О типологических особенностях текста Евангелия Тип-7 из собрания РГАДА ф. 381, № 7 - Szwed, Zofia (Acta Polono-Ruthenica, 2017)
The article is devoted to the 13th century Gospel Book, which is kept in the Russian State Archive of Old Records and registered under reference F. 381, № 7. The aim of the paper is to define the similarity of the manuscript to other old texts according to its content and order of readings. Moreover, the author attempts to find the Gospel Book’s place in the classification of full lectionaries. In the course of the analysis it is stated that the text has various typological features. Despite the fact that in some elements it resembles the South Slavonic Miroslav Gospel, it belongs to the most common type of full lectionaries in Ruthenia among which the leading role is played by Mstislav Gospel. Furthermore, the manuscript reflects the peculiar features of Milata Gospel, which makes it a part of the class of manuscripts represented by this old text of Novgorod.